2022
DOI: 10.1101/2022.02.13.480245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clock Work: Deconstructing the Epigenetic Clock Signals in Aging, Disease, and Reprogramming

Abstract: Epigenetic clocks have come to be regarded as powerful tools for estimating aging. However, a major drawback in their application is our lack of mechanistic understanding. We hypothesize that uncovering the underlying biology is difficult due to the fact that epigenetic clocks are multifactorial composites: They are comprised of disparate parts, each with their own causal mechanism and functional consequences. Thus, only by deconstructing epigenetic clock signals will it be possible to glean biological insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 53 publications
(98 reference statements)
2
40
0
Order By: Relevance
“…Likewise, while the Horvath, PhenoAge, SkinBlood, and Hannum clocks, which were all trained in some manner on chronological age, are also comprised of mortality-associated modules, they contain additional submodules that have weak or inverse associations with mortality (68). This suggests a connection between our findings and mortality or cardiovascular risk in particular as opposed to tumorigenesis or other age-related cellular processes that appear to be captured more strongly by other clocks.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Likewise, while the Horvath, PhenoAge, SkinBlood, and Hannum clocks, which were all trained in some manner on chronological age, are also comprised of mortality-associated modules, they contain additional submodules that have weak or inverse associations with mortality (68). This suggests a connection between our findings and mortality or cardiovascular risk in particular as opposed to tumorigenesis or other age-related cellular processes that appear to be captured more strongly by other clocks.…”
Section: Discussionmentioning
confidence: 69%
“…We did not identify any effects for the Horvath, SkinBlood, Hannum, or PhenoAge clocks, which is consistent with prior research that found stronger associations between socioeconomic disadvantage and GrimAge EAA and DunedinPoAm (3739). Because epigenetic aging measures are composite indicators that are comprised of many different DNAm patterns, a major drawback of their application is a lack of mechanistic understanding of what they are capturing, both in terms of how environmental processes may be initiating these changes as well as their connection to disease etiology (68, 69). Of note, a recent study deconstructed over 5,000 clock CpGs into twelve distinct submodules that display different biological underpinnings and vary considerably in their proportion across clocks (68).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often discussed within the field that CpGs-at least those on the Illumina array technologies-change in a concerted, multi-collinear manner with age. This has motivated some of our prior approaches to clustering clock CpGs to ascertain underlying biological signals or changes [53,54]. We find that the vast majority of CpGs selected by clocks do tend to be unique to those clocks, though a small subset of methylation sites are common across many clocks within categories (Figure 4A-B).…”
Section: Resultsmentioning
confidence: 82%